Formation of Confident Character in Students and the Role of Guidance and Guidance Teachers: Case Study in High School - Satriani, Lia; Atmoko, Adi; Ramli, M. (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
Self-confidence is one of the factors with which students can interact well socially at school. Through this character, students are able to independently solve problems and generate positive feelings for others. The aim of this research is to look at 1) the description of students' self-confidence in high school, 2) determining the self-confident character of students in high school, and 3) the role of counselors in their contribution to developing students' self-confident character in high school. This research uses a qualitative case study design. The location of the research was SMA Swasta Budi Agung Medan. The data sources were selected using the technique of purposive sampling. Data collection techniques use in-depth interviews, observation, and documentation methods. The validity of the data in this research uses data triangulation techniques. The results of this research are: the self-confident character of students in this school can grow through being active in academic and non-academic activities, supported by teachers who have pleasant personalities. A counselor also helps identify personality, personal potential, and the type of career that is suitable for students through the MBTI test, carries out counseling both individually and groups, collaborates with parents, and also continues to provide support and motivation.